Systematic literature review on public engagement via government social media during the COVID-19 crisis - Guo, Jingjing; Mohd Zawawi, Julia Wirza; Kamarudin, Syafila (Redfame Publishing, 2024)
Public engagement on government social media platforms can boost public trust in government while also improving and speeding up the distribution of health information. The importance of public engagement and its widespread existence have promoted extensive academic research on this channel. The purpose of this systematic literature review is to identify and bridge gaps in theories and conceptual frameworks in studies of public engagement via government social media. Furthermore, the objective of this research is to establish a comprehensive framework for analyzing how the public's engagement on government social media during the COVID-19 pandemic is affected by elements including information quality, source credibility, social media characteristics, and personal trust. The PRISMA method is used to review publications from 2019. After an extensive systematic review procedure that involved searching for relevant publications and utilizing inclusion and exclusion criteria to retrieve those that met the study's purpose, 32 papers were finally selected from the Scopus and Google Scholar databases. Finally, this study's findings shed light on the interactions between the public and the government during COVID-19 and offer recommendations for further research on public engagement, including more diverse social media types, the expansion of public engagement forms on social media, and the adoption of different theory or model. This study provides more evidence for research on public online engagement and offers some practical implications for effective communication between governments and the public.